EFFICACY AND SAFETY OF CONVENTIONAL EPIDURAL VERSUS COMBINED SPINAL EPIDURAL IN PERCUTANEOUS NEPHROLITHOTOMY: A PROSPECTIVE AND RANDOMIZED CLINICAL STUDY - Rathore, Vikram Singh; Prasad, Sarita; D, Harsha; Sharma, Charu; Partani, Seema (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to compare the efficacy and safety of conventional epidural (ED) versus combined spinal epidural (CSE) in percutaneous nephrolithotomy (PCNL) with addition of opiods and dexmedetomidine. Methods: This prospective, randomized, and double-blinded clinical study was conducted in the in patients undergoing PCNL. Group CSE had received CSE anesthesia and Group ED given conventional epidural anesthesia. Time to first rescue analgesic and total dose of rescue analgesic along with hemodynamic parameters were compared up to 24 h. Patient, surgeon satisfaction score, and post-operative complications were also compared. Results: Time from onset of sensory block to first requirement of analgesia was prolonged in group CSE (218.4±18.30 min) as compared to Group ED (210±17.88 min). (p<0.001) Mean time for first rescue analgesia postoperatively was highly significant in group CSE (2.42±0.49) as compared to Group ED (2.08±0.28). (p<0.0001) Total dose of levobupivacaine required was high in Group ED (49.66±7.02) as compared to Group CSE (45.66±3.12). (p<0.001) In Group ED, surgeon score was good in 20 (44.44%) patients and which was highly significant. In Group CSE, surgeon score was excellent in 41 (91.1%) patients and which was highly significant. (p<0.001) Post-operative complications in both the group were comparable (p>0.05). Conclusion: This study concluded that though both the anesthesia techniques are safe and efficient with each having its own benefits. CSE had proven superiority over the epidural technique.